Impacts of Cumulus Parameterization Schemes on the Simulation of Interannual and Interdecadal Variation of Meiyu in the Middle and Lower Reaches of the Yangtze River by Using Regional Climate Model 4 - Hu, Yijia; Zhong, Zhong; Ha, Yao; Sun, Yuan; Zhu, Yimin; Yu, Lijun (Frontiers in Earth Science, 2020)
This study has revealed the impacts of cumulus parameterization scheme (CPS) on the simulation of interannual and interdecadal variations of Meiyu in the middle and lower reaches of Yangtze River valley (YangtzeMeiyu) by using a regional climate model. A multiple 55-yr (1955-2009) simulation of YangtzeMeiyu is conducted using RegCM4.6 with different CPSs, including Emanuel scheme, Kuo scheme and Grell scheme. It is found that all the CPSs have good performances and strong convergence in simulating the interannual variation of YangtzeMeiyu rainfall amounts. However, large bias are found in the simulated interdecadal variation of YangtzeMeiyu rainfall amount by the three CPSs. Because the Emanuel CPS has good performance in the simulation of both interannual and interdecadal variations of YangtzeMeiyu, its overall performance in the simulation of total amount of YangtzeMeiyu is the best among the three CPSs. The second best CPS is the Grell scheme, and the worst is the Kuo scheme. The model convergence in simulating the distribution of YangtzeMeiyu shows an obvious characteristic of interdecadal variation. During the years with strong summer monsoon and northward rain belt, the simulated distributions of YangtzeMeiyu by the three CPSs are quite different, and the model convergence is weak. On the contrary, during the years with weak summer monsoon and southward rain belt, the simulated distributions of YangtzeMeiyu by the three CPSs are similar with each other, and the model convergence is strong. As a result, when the well-known interdecadal change happens in the late 1970s, the monsoon changes from strong to weak, whereas the model convergence changes from weak to strong.